Cross-sectional associations between ambient air pollution and respiratory signs and symptoms among young children in Tehran. (15th February 2020) - Namvar, Zahra; Yunesian, Masud; Shamsipour, Mansour; Hassanvand, Mohammad Sadegh; Naddafi, Kazem; Shahhosseini, Elahe
Abstract: Exposure to ambient air pollutants may significantly affect the incidence of respiratory symptoms and lung function in children. The present study examined the associations between exposure to ambient air pollutants and respiratory symptoms in children. In this cross-sectional study, 1070 children under the age of seven years were recruited from 61 day-care centers of Tehran in 2015. Initially, day-care centers were selected at a radius of 2 km from the air pollution monitoring stations, and subsequently all the children attending these day-care centers were interviewed. The data on the respiratory complaints of children were obtained by using the ATS questionnaire (ATS-DLD-78-C). Moreover, the annual average concentration of pollutants was calculated based on the time children spent at home and at the day-care center using the air pollution monitoring stations. Crude and adjusted logistic regression analysis was conducted. The findings indicated that ambient air SO2 and NO2 concentrations near home were associated with current asthma for 1 part per billion (ppb) increase with an OR of 1.20 (1.00–1.45) and 1.08 (1.01–1.15), respectively. The odds of developing persistent phlegm for each unit (ppm) of raise in the average annual concentration of CO in ambient air near home (OR 1.40; 1.09 to 1.81) increased as well. The daily mean concentration of PM2.5, PM10, and SO2 was higher than the limits provided in the World Health Organization (WHO) air quality guidelines (AQGS ). Moreover, the prevalence of severe wheezing, asthma history, and bronchitis was higher in boys. Therefore, long-term exposure to ambient air pollutants such as SO2, NO2, and CO may be associated with an increase in current asthma and persistent phlegm in children. Graphical abstract: Image 1 Highlights: Ambient air pollution in Tehran increase respiratory symptoms in children under the age of seven. Long-term exposure to NO2, SO2 and CO ambient air near the home increases current asthma and persistent phlegm in children. The respiratory signs and symptoms of severe wheezing, asthma history, and bronchitis were more common in boys.